DIGITAL PLATFORMS OF GOVERNMENT SERVICES: PROBLEMS, OPPORTUNITIES AND ILLUSIONS (Вестник университета)
Public services, being the central process of society, requires constant improvement. To define the direction of modernization the article covers the assessment of the current level of existing electronic services. Based on the public opinion research, the analysis of the main problems making getting services difficult is carried out. The main characteristics that qualitative service should possess, are defined, among which are availability and relevance. The work also focuses on the need to study the current level of digitalization, which helps to create an emergent view of the existing system and to generate ideas for reorganization and optimization in order to maximize the benefits to society.